Classical theories of gravity produce entanglement - Joseph Aziz; Richard Howl (Nature, 2025)
Abstract The unification of gravity and quantum mechanics remains one of the most profound open questions in science. With recent advances in quantum technology, an experimental idea first proposed by Richard Feynman 1 is now regarded as a promising route to testing this unification for the first time. The experiment involves placing a massive object in a quantum superposition of two locations and letting it gravitationally interact with another mass. If the two objects subsequently become entangled, this is considered unambiguous evidence that gravity obeys the laws of quantum mechanics. This conclusion derives from theorems that treat a classical gravitational interaction as a local interaction capable of transmitting only classical, not quantum, information 2–8 . Here we extend the description of matter used in these theorems to the full framework of quantum field theory, finding that theories with classical gravity can then transmit quantum information and, thus, generate entanglement through physical, local processes. The effect scales differently to that predicted by theories of quantum gravity, and so it gives information on the parameters and form of the experiment required to robustly provide evidence for the quantum nature of gravity.